UPAYA MENINGKATKAN PEMAHAMAN TENTANG SEMANGAT MENUNTUT ILMU DAN MENGAMALKANNYA MELALUI MEDIA FILM RELIGI PADA SISWA KELAS X.IPS SMA NEGERI 2 SKANTO TAHUN PELAJARAN 2019/2020 - Masulita Karmila (honai, 2021)
ABSTRACT Based on the explanation of the study problems, the researchers are interested in conducting a research entitled "The Use of Religious Film Media in Improving Students' Understanding of the Spirit looking for a science and Practicing It in the ten grade students in social science class state senior high school 2 Skanto in the academic year 2019/2020." The student learning outcomes continue to increase from pre-cycle to cycle 2. In the pre-cycle, the number of students who have completed learning is only 36%. Then in cycle 1, the number of students who finished studying was 63%. In cycle two, the number of students who finished studying was 89%. So the researchers made conclusions from the results of research conducted in the ten grade students in social science class at state senior high school 2 Skanto in the academic year 2019/2020, namely: applying of religious film media in increasing students' understanding of the spirit of studying and practicing it for the ten grade students in social science class at state senior high school 2 Skanto in the academic year 2019/2020 has been right on target and has been successfully implemented. Keywords: Improving, Understanding, Religious Film Media. ABSTRAK Penelitian ini bertujuan untuk mengetahui pemahaman tentang semangat menuntut ilmu dan mengamalkannya melalui penggunaan media film religi pada siswa Kelas X.IPS SMA Negeri 2 Skanto Tahun Pelajaran 2019/2020. Metode yang digunakan adalah deskriptif kualitatif dengan menggunakan siklus penelitian. Setiap siklus dilaksanakan 2 kali pertemuan dengan tahapan pelaksanaan tindakan meliputi empat Langkah (1) perencanaan tindakan; (2) pelaksanaan tindakan; (3) Pengamatan; (4) refleksi. Hasil penelitian menunjukkan bahwa jumlah siswa yang tuntas belajar hanya 36%, pada siklus 1 jumlah siswa yang tuntas belajar 63%, dan pada siklus 2 jumlah siswa yang tuntas belajar 89 %. Maka peneliti membuat kesimpulan dari hasil penelitian yang dilakukan di Kelas X.IPS SMA Negeri 2 Skanto Tahun Pelajaran 2019/2020, yaitu: penggunaan media film religi dalam meningkatkan pemahaman siswa tentang semangat menuntut ilmu dan mengamalkannya pada siswa kelas X.IPS SMA Negeri 2 Skanto Tahun Pelajaran 2019/2020 telah tepat sasaran dan berhasil dilaksanakan. Kata kunci : Meningkatkan, Pemahaman, Media Film Religi.